Técnicas de ensaio coral: reflexões sobre o ferramental do Maestro Carlos Alberto Pinto Fonseca - Willsterman Sottani Coelho (2009)
This research was conducted in view of the uniqueness and importance of Maestro Carlos Alberto Pinto Fonsecas work throughout his career as titular conductor of Ars Nova - Coral da UFMG. In order to contribute to the rescue of Brazils artistic and cultural memory and to fill many gaps in the technique universe in the area of Choral Conducting, the resources that constitute the Maestros rehearsal technical tools (conductors psychological profile, preparing the group, repertoire settings and technical artistry) were collected and systematized, and his historical trajectory (his musical improvement and Ars Nova direction) and the original sources of that tools (especially the school of Robert Shaw) were discussed.